Mesenchymal hamartoma of the chest wall in an infant - A benign entity masquerading as malignancy - Harshavardhan Mahalingam; Madhu Ramasundaram; Swaminathan Rajendiran; Dhaarani Jayaraman (Wolters Kluwer Medknow Publications, 2021)
Mesenchymal hamartoma of the chest wall is a rare tumor-like lesion encountered in neonates and infants. Although typically benign with no metastatic potential, it has alarming imaging and pathological features that mimic malignancy. We describe the imaging, surgical, and pathological features of this rare entity in a 1-month-old infant.